Culturally relevant science teaching: possible connection of socio-cultural knowledge with present science curriculum of Nepal - Kamal Prasad Koirala; Bishnu Bahadur Khatri (Discover Education)
Abstract This study aims to examine the connection of culturally relevant science pedagogy to school science teaching in Nepali context. A library research and meta-analysis approach was employed to gather relevant books, articles, reports, and theories on Culturally Relevant Science Teaching (CRST) to explore its connection to sociocultural knowledge in science teaching. The findings of the study indicate that CRST necessitates the integration of sociocultural knowledge to help students develop socio-political consciousness. Both Vedic and Ethno-science contain significant socio-culturally embedded science, with spiritual practices being one example. The education policy of Nepal also advocates for the inclusion of such spiritual science in the school science curriculum. However, curriculum designers, textbook writers, students, and teachers demonstrate reluctance to incorporate these elements into the curriculum. Without integrating historically and socioculturally emerged science into the modern school science curriculum, it is not possible to link CRST to the socio-political consciousness of students. These findings imply that science teachers require further input in designing culturally relevant activities that connect to school science, which can be provided through professional development programs.